PENGARUH AKTUALISASI DIRI DAN PENGHARGAAN TERHADAP PRESTASI KERJA KARYAWAN PADA PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA MUARE ULAKAN KABUPATEN SAMBAS DALAM PERSPEKTIF BISNIS ISLAM - Juliana; Gustina; maskupah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
The potential of human resources must be managed as well as possible in order to provide optimal output. Therefore, a company must think about ways it can develop the potential of its employees. One of them is improving employee work performance, good work performance will provide benefits for employees and the company. Work performance is influenced by various factors, including self-actualization and appreciation. Employees who have the opportunity to actualize themselves and receive appropriate rewards tend to have high motivation to participate. This research aims to determine the effect of Self-Actualization and Reward on Employee Work Performance at the Tirta Muare Ulakan Regional Public Water Company, Sambas Regency, both partially and simultaneously. This research method uses quantitative research with causal associative research. The data used is primary data and secondary data. Primary data sources were obtained through distributing questionnaires to all employees in the company and then tested using the SPSS version 22 application with validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple regression tests, hypothesis tests and coefficient of determination tests. Meanwhile, secondary data was obtained from documents from offices related to this research. These results show that the self-actualization variable has a positive and significant effect on employee work performance at the Tirta Muare Ulakan Regional Public Water Company, Sambas Regency with a value of Tcount>Ttable (6.431>3.315) or can be seen from Siga (0.000<0.005). Apart from that, the reward variable also shows a positive and significant influence on employee work performance at the Tirta Muare Ulakan Regional Public Water Company, Sambas Regency with a Tcount value of Ttable (3.947>3.315) or can be seen from Sig<a (0.000<0.005). Simultaneously, self-actualization and appreciation have a positive effect on employee work performance at the Tirta Muare Ulakan Regional Public Water Company, Sambas Regency with a Tcount Ttable value (200.142>3.315) and a Sig value <0.05 (0.000<0.05)